A Review of Methods Employed to Identify Flicker Producing Sources - Jeevan Inamdar; K. Iyswarya Annapoorani (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
Because of increasing requirements of the present consumers and industrial units utilizing sensitive loads, there is need of good power quality in order to retain the power quality standards. Nowadays the study of the voltage flicker is becoming essential part of power quality studies. The flicker is typically the effect of a rapidly changing load which is large with respect to the short circuit ability of an electrical supply system. The inferior effects of voltage flicker include malfunctioning of power electronic equipment. Also it causes annoying effects to human. Hence detection of the flicker source is an essential step in the power quality assessment process. This paper delivers a review about methods used to identify flicker producing loads in accordance with IEC 61000-4-15. Once the report related to the disturbance place is known, an investigation and corrective action can be accordingly carried out. Also a method based upon Discrete Wavelet Transform and Artificial Neural Network is proposed to detect initial instance of occurrence of flicker.